DECRIMINALIZING SUICIDE: A REVIEW WITH ISLAMIC PERSPECTIVES (International Seminar on Syariah and Law (INSLA), 2023)
The recent decriminalization of suicide in Malaysia is the subject of this study, which specifically looks at it from an Islamic perspective. Using a qualitative research methodology, the study thoroughly reviews the literature, including both articles and research papers. The main objective is to identify obstacles and offer suggestions related to decriminalization. Religious perspectives and cultural implications are major areas of analysis. The goal of the study is to present a thorough grasp of the implications of decriminalizing suicide considering Islamic teachings. The research explores legal, cultural, and religious aspects while concentrating on barriers to implementing global policies and the stigma associated with mental illness that prevents people from seeking help. It makes suggestions for how Islamic organizations can actively address mental health issues in Malaysia and provides advice for helping those who suffer from mental illness that is based on Islamic principles. The expected results are intended to add to the conversation about mental health, Islamic perspectives, and international guidelines by offering sophisticated perspectives to researchers, policymakers, and Islamic organizations involved in these conversations. The study emphasizes how important it is for the Islamic community to work together to eliminate stigma and create a welcoming atmosphere for mental health.